Development of Cytomegalovirus (CMV) Immune Recovery Uveitis Is Associated with Th17 Cell Depletion and Poor Systemic CMV-Specific T Cell Responses - Hartigan-O'Connor, Dennis J.; Jacobson, Mark A.; Tan, Qi Xuan; Sinclair, Elizabeth (Clinical infectious diseases, 2011)
Background. The immune reconstitution inflammatory syndromes (IRIS) are a spectrum of inflammatory conditions associated with opportunistic infections and occurring in ∼16% of human immunodeficiency type 1 (HIV-1)-infected patients given antiretroviral therapy. It has been proposed that these conditions are linked by a dysregulated immune system that is prone to exaggerated responses. However, immunologic studies have been limited by the availability of longitudinal samples from patients with IRIS and appropriate matched control subjects. Cytomegalovirus (CMV) immune recovery uveitis (IRU) is an IRIS occurring in up to 38% of patients with CMV retinitis. Although the pathologic immune responses occur in the eye, immune dysregulation that allows for development of pathologic responses is presumably caused by faulty systemic immune cell reconstitution. Methods. We examined CMV-specific T cell responses, regulatory T (T reg ) cell function and polyclonal T cell responses, including IL-17 production, in 25 patients with CMV IRU and 49 immunorestored control subjects with CMV retinitis who did not develop IRU. Results. Patients with CMV IRU had poor CMV-specific CD4 + T cell responses, as compared with control subjects, whereas CD8 + T cell responses were comparable. Patients with CMV IRU were characterized by smaller numbers of circulating Th17 cells. Deficiency in anti-CMV responses was not associated with differences in T reg cell function. Conclusions. The T reg cell compartment is intact in patients with CMV IRU, and these patients do not develop exaggerated systemic CMV-specific or polyclonal immune responses. Cases are instead characterized by more profound depletion of Th17 cells and poor antiviral immune responses. CMV IRU may be most likely to develop in persons experiencing the greatest degree of immune dysfunction before initiating highly active antiretroviral therapy.